Impact of Supply Chain Management on the Indian SME Operational Effectiveness - Dr B R Celia, Subharun Pal, Om Prakash C, Sameer Yadav, Dr. Mahendranath Chowdary, Dr Veeramani G (Journal of Informatics Education and Research, 2023)
Supply Chain Management (SCM) operational effectiveness refers to the ability of an organization to efficiently and smoothly execute its supply chain processes to achieve its strategic goals. This involves streamlining processes, minimizing waste, and leveraging technology to enhance visibility and control across the entire supply chain network. The efficacy of a supply chain is a critical determinant of an organization's success and competitiveness in today's globalized business environment. When effectively managed, it can lead to numerous advantages, such as reduced costs through streamlined processes and minimized waste, improved customer satisfaction through timely and accurate deliveries, and enhanced responsiveness to market fluctuations. It also helps in optimizing inventory levels, reducing working capital requirements, and promoting sustainability by minimizing environmental impact. The study concluded that the efficacy of a supply chain is not just a cost-saving measure; it is a strategic asset that can drive growth, profitability, and long-term success for businesses in a highly interconnected and rapidly evolving world.